Recent advances in human viruses imaging studies. (5th April 2016) - Florian, Paula Ecaterina; Rouillé, Yves; Ruta, Simona; Nichita, Norica; Roseanu, Anca
Abstract : Microscopy techniques are often exploited by virologists to investigate molecular details of critical steps in viruses' life cycles such as host cell recognition and entry, genome replication, intracellular trafficking, and release of mature virions. Fluorescence microscopy is the most attractive tool employed to detect intracellular localizations of various stages of the viral infection and monitor the pathogen‐host interactions associated with them. Super‐resolution microscopy techniques have overcome the technical limitations of conventional microscopy and offered new exciting insights into the formation and trafficking of human viruses. In addition, the development of state‐of‐the art electron microscopy techniques has become particularly important in studying virus morphogenesis by revealing ground‐braking ultrastructural details of this process. This review provides recent advances in human viruses imaging in both, in vitro cell culture systems and in vivo, in the animal models recently developed. The newly available imaging technologies bring a major contribution to our understanding of virus pathogenesis and will become an important tool in early diagnosis of viral infection and the development of novel therapeutics to combat the disease.